Pengaruh Model Discovery Learning Terhadap Hasil Belajar Matematika Materi Penyajian Data di Kelas V Sekolah Dasar - Dhea, Fadisya Ivana; Masniladevi, Masniladevi (Universitas Negeri Padang, 2024)
This research was conducted to determine the effect of the Discovery Learning model on mathematics learning outcomes on data presentation material in class V SDN Gugus III Sijunjung District. The type of research used in this research is Quasi Experiment using a quantitative approach. The Quasi Experiment design used is a Nonequivalent Control Group Design. The sampling technique in this study was cluster random sampling. The data collection technique in this study was to use a test instrument. The population part of this study is all fifth-grade students of SDN Gugus III Koto VII District, Sijunjung Regency. The instrument used in this study is a learning outcome test, to prove the hypothesis in this study, hypothesis testing is carried out using the t-test. after learning using the Discovery Learning model, the results of the posttest of students in learning mathematics presentation data material show that the average value of the experimental class is higher than the control class, namely 80.00 (experimental class) and 64.77 (control class). The results of data analysis from hypothesis testing show tcount = 3.8055 and ttable = 2.2021. So that tcount> ttable, then H0 is rejected and Ha is accepted. The conclusion of this study is that there is an effect of the Discovery Learning model on student learning outcomes.